Electrospun poly(acrylic acid)/poly(vinyl alcohol) nanofibrous adsorbents for Cu(ii) removal from industrial plating wastewater. Issue 29 (24th March 2017) - Park, Jeong-Ann; Kang, Jin-Kyu; Lee, Seung-Chan; Kim, Song-Bae
Abstract : Nanofibrous adsorbents were fabricated by electrospinning with a blend solution of poly(acrylic acid) (PAA) and poly(vinyl alcohol) (PVA) polymers and used for copper (Cu(ii )) removal from industrial plating wastewater. Abstract : Nanofibrous adsorbents were fabricated by electrospinning with a blend solution of poly(acrylic acid) (PAA) and poly(vinyl alcohol) (PVA) polymers and used for copper (Cu(ii )) removal from industrial plating wastewater. Fourier-transform infrared spectrometry analysis demonstrated that a new peak appeared at 1617 cm −1 due to the interactions between Cu(ii ) and carboxyl oxygen on the surfaces of the PAA/PVA nanofibrous adsorbents during Cu(ii ) removal in the plating wastewater. X-ray photoelectron spectroscopy analysis showed that the Cu 2p peak at a binding energy of 932 eV appeared in a wide scan of the nanofibrous adsorbents after Cu(ii ) removal in the plating wastewater. The carboxyl groups on the surfaces of the nanofibrous adsorbents could provide sorption sites for Cu(ii ) removal. Laboratory experiments in synthetic solutions showed that the nanofibrous adsorbents were effective in Cu(ii ) removal. The nanofibrous adsorbents had a maximum Cu(ii ) removal capacity of 49.3 mg g −1 with a far higher selectivity for Cu(ii ) over Ni(ii ) in a binary system. Also, the nanofibrous adsorbents could be regenerated and reused for Cu(ii ) removal through successive adsorption–desorption processes. Batch experiments in industrial plating wastewater (Cu(ii ) concentration = 430.06 mg L −1 ) demonstrated that the nanofibrous adsorbents had Cu(ii ) removal capacity of 25.8–33.6 mg g −1 in the adsorbent dose of 0.4–2.0 g L −1 . However, the removal of other heavy metal ions (Ni, Zn, etc. ) in the wastewater by the nanofibrous adsorbents was negligible. The nanofibrous adsorbents were also applied through filtration tests for Cu(ii ) removal from the wastewater under dynamic flow conditions.